2013
DOI: 10.3389/fpsyt.2013.00060
|View full text |Cite
|
Sign up to set email alerts
|

Interindividual Variability in Stress Susceptibility: A Role for Epigenetic Mechanisms in PTSD

Abstract: Post-traumatic stress disorder (PTSD) is a psychiatric condition characterized by intrusive and persistent memories of a psychologically traumatic event that leads to significant functional and social impairment in affected individuals. The molecular bases underlying persistent outcomes of a transient traumatic event have remained elusive for many years, but recent studies in rodents have implicated epigenetic modifications of chromatin structure and DNA methylation as fundamental mechanisms for the induction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 304 publications
(485 reference statements)
1
49
0
Order By: Relevance
“…Stressful stimuli alter DNA methylation state (see above) (e.g. Zovkic et al, 2013b) and this increased methylation may result from upstream events, including increased glutamate transmission, neuropeptide transmission and increased transcription factor activation (Stankiewicz et al, 2013). The presence of CE is clearly a stressor for Lymnaea Lukowiak et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Stressful stimuli alter DNA methylation state (see above) (e.g. Zovkic et al, 2013b) and this increased methylation may result from upstream events, including increased glutamate transmission, neuropeptide transmission and increased transcription factor activation (Stankiewicz et al, 2013). The presence of CE is clearly a stressor for Lymnaea Lukowiak et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Following pioneering work that indicated that differential methylation of the GR gene mediated the effects of different mothering styles on stress responses and maternal behavior in rats 166 , substantial evidence has shown that different components of the HPA axis are highly susceptible to epigenetic modulation by stress. Conversely, glucocorticoids themselves are important regulators of the epigenome 165 . Although the precise link with social behaviors is still scarce, the importance of these mechanisms in the link between stress and the social brain is illustrated by several examples.…”
Section: Epigenetic Mechanismsmentioning
confidence: 99%
“…An exploding body of evidence provides strong support for key roles of epigenetic mechanisms in mediating the effects of stress on brain and behavior, including gene-environment interactions at different developmental periods (for reviews, see 55,165 ). By regulating gene transcription, epigenetic mechanisms contribute to the effects of both stressors experienced in adulthood that have an immediate impact and those experienced early in life that have long-lasting effects on adult behavior and brain function.…”
Section: Epigenetic Mechanismsmentioning
confidence: 99%
“…Recent studies have shown that epigenetic mechanisms are important for successful adaptation to a stressful environment and have a role in the development of PTSD (Zovkic et al, 2013). DNA methylation is an important epigenetic mechanism that is influenced by genetic and environmental factors (Malan-Muller et al, 2014), and reflects the transcriptional status of a particular gene (Schubeler, 2015).…”
Section: Introductionmentioning
confidence: 99%